From the history of Komi-Permian ethnography: Lyubov Stepanovna Gribova. To the 90th anniversary of his birth - Chernykh, A.V.; Vaiman, D.I. (Perm Federal Research Centre Journal, 2023)
The article сonsiders the biography of the well–known researcher of ethnography of the Komi peoples, Lyubov Stepanovna Gribova, on the basis of archival and published sources. The basic information about the scientist’s biography is given, including the peculiarities of field research among the Permian Komi. The article analyzes the main scientific works of the researcher.